A Discourse Analysis On Conversation Of “Who is The Ideal Presidential Candidate for Young People” On Mata Najwa - Putri, Ni Made Wilhel Mina (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to understand and describe the model of speech from the results of interviews that occurred in the conversation "Who is the Ideal Candidate for Young People" in Mata Najwa and this can be used as a useful language teaching tool. This research is a research with a descriptive qualitative method. Data collection was carried out by recording and note-taking techniques. Data analysis was carried out through several procedures: (1) data reduction (data selection and data coding), (2) data presentation, and (3) drawing conclusions and data verification. Based on the results of data analysis and discussion, the conclusion of this research is that the researcher found a functiona form of conversational implicature in Mata Najwa's interactive dialogue with public officials. By using the theory of conversation analysis with several aspects in it such as opening and closing analysis, adjecency pairs, topic management, turn-taking, preference organization, feedback, and improvement, in accordance with the theory of conversation analysis in discourse analysis.